THE EFFECT OF CELEBRITY ENDORSEMENT, PERCEIVED QUALITY, AND BRAND LOYALTY ON PURCHASE INTENTION (CASE STUDY: SULWHASOO COSMETIC PRODUCTS) - Dewi S.S Wuisan; Jane Angela (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract. This study aims to examine how the influence of celebrity endorsement, perceived quality, and brand loyalty on purchase intention. Along with the times, many companies are implementing sales strategies by using celebrities in advertising their products. Celebrities are believed to be able to increase sales figures because people in increasingly sophisticated technological developments are more likely to use the internet as access using social media as entertainment to view various kinds of films, content, and the like to see the lives of celebrities to be used as models as part of their lifestyle. . The use of celebrities in advertising greatly affects sales figures. Likewise, perceived quality and brand loyalty are influential in sales. Perceived quality is the quality of a product where users of the product have felt the benefits so that they continue to buy the product, while brand loyalty is loyalty to a brand that is believed to have good quality because the brand has been recognized. In this study, we examine the effect of these three variables on the purchase intention of Sulwashoo cosmetic products from Korea, which for the past four years have gone viral on social media endorsed by a celebrity, namely Song Hye Kyo. Celebrity endorsement, and perceived quality, have a positive effect on purchase intention and brand loyalty too.Abstrak. Penelitian ini bertujuan untuk menguji bagaimana pengaruh celebrity endorsement, perceived quality, dan brand loyalty terhadap purchase intention. Seiring dengan perkembangan zaman, banyak perusahaan yang menerapkan strategi penjualan dengan memanfaatkan selebritis dalam mengiklankan produknya. Selebriti diyakini mampu meningkatkan angka penjualan karena masyarakat dalam perkembangan teknologi yang semakin canggih lebih cenderung menggunakan internet sebagai akses menggunakan media sosial sebagai hiburan untuk melihat berbagai macam film, konten, dan sejenisnya untuk melihat kehidupan selebriti hingga dijadikan model sebagai bagian dari gaya hidup mereka. . Penggunaan selebriti dalam iklan sangat mempengaruhi angka penjualan. Demikian juga, persepsi kualitas dan loyalitas merek berpengaruh dalam penjualan. Perceived quality adalah kualitas suatu produk dimana pengguna produk tersebut telah merasakan manfaatnya sehingga mereka terus membeli produk tersebut, sedangkan brand loyalty adalah loyalitas terhadap suatu merek yang diyakini memiliki kualitas yang baik karena merek tersebut telah diakui. Dalam penelitian ini, kami menguji pengaruh ketiga variabel tersebut terhadap niat beli produk kosmetik Sulwashoo asal Korea yang selama empat tahun terakhir viral di media sosial yang di-endorse oleh seorang selebriti, yaitu Song Hye Kyo. Dukungan selebriti, dan kualitas yang dirasakan, memiliki efek positif pada niat beli dan loyalitas merek juga.